SCIENTIFIC AND THEORETICAL VIEWS ON IMPROVING THE EFFICIENCY OF ADVERTISING SERVICES IN AN INNOVATIVE ECONOMY - Samieva, Gulnoza Tokhirovna; Djurayeva, Roziya Kahramon kizi (THE INNOVATION ECONOMY, 2026)
This article provides a comprehensive analysis of scientific research conducted by domestic scholars, researchers from CIS countries, and foreign authors on the issues of improving the efficiency of advertising services in the context of an innovative economy. The study examines the economic essence of advertising services, their role in enhancing the competitiveness of business entities, and their relationship with innovation-driven development processes. Based on the review of scientific literature, the key factors determining the effectiveness of advertising services are systematized, including the use of digital technologies, Big Data tools and marketing analytics, the development of social media marketing, as well as modern mechanisms influencing consumer behavior. Furthermore, the article substantiates the main directions for improving the efficiency of advertising services under the conditions of an innovative economy and formulates scientific conclusions and practical recommendations aimed at enhancing the effectiveness of advertising activities.